An outbreak of Australian Stringhalt associated with skin lesions in Colombia - Oliver, Olimpo J; Suárez, Juan C (Revista Colombiana de Ciencias Pecuarias, 2016)
eight Silla Argentina breed horses imported from Argentina presented with an abnormal gait and skin lesions. Clinical and laboratory findings: all cases showed different degrees of hind limb hyperflexion, atrophy of the lateral digital muscles, skin lesions, and poor body condition. They underwent several clinical and laboratory examinations, including endoscopy of the upper respiratory tract, skin and liver biopsy, blood count, biochemical profile, and electromyography that showed evidence of a neuropathy and dermatitis. Treatment approach: the horses were treated with phenylbutazone and thiamine. The response was patient dependent with different degrees of recovery resulting. Conclusion: this is the first report of an outbreak of bilateral Australian Stringhalt in Colombia and the first associated to skin lesions according to the veterinary medicine scientific literature.